2015
DOI: 10.1103/physrevb.92.045432
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tunneling density of states at a Y junction of spin-12Tomonaga–Luttinger liquid wires

Abstract: We calculate the tunneling density of states (TDOS) in a dissipationless three wire junction of interacting spin-1/2 electrons, and find an anomalous enhancement of the TDOS in the zero bias limit, even for repulsive interactions for several bosonic fixed points. This enhancement is physically related to the reflection of holes from the junction for incident electrons, and it occurs only in the vicinity of the junction (x < vmin/2ω where vmin is the minimum of the velocity of charge or spin excitations and ω i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…At the C ± fixed points, the leading term in the OPE of the boundary SSCO is proportional to the identity. This is consistent with the fact that the boundary interaction in (10) is responsible for pinning the bosonic fields through chiral boundary conditions, similarly to other applications of the method of delayed evaluation of boundary conditions [26, 59,60]. As a result, we find a nonzero expectation value,…”
Section: The Boundary Phase Diagramsupporting
confidence: 89%
“…At the C ± fixed points, the leading term in the OPE of the boundary SSCO is proportional to the identity. This is consistent with the fact that the boundary interaction in (10) is responsible for pinning the bosonic fields through chiral boundary conditions, similarly to other applications of the method of delayed evaluation of boundary conditions [26, 59,60]. As a result, we find a nonzero expectation value,…”
Section: The Boundary Phase Diagramsupporting
confidence: 89%
“…Understanding quantum effect in three terminal junctions is important for potential applications as rectifiers [2,3], switches, and logic gate devices [4]. Recently, these systems have also been studied theoretically [5][6][7][8][9][10][11][12]. Interesting predictions include a low energy chiral fixed point with an asymmetric current flow in a spinless fermionic system [13] and negative density reflection at the junction of Bose liquid of ultracold atoms [14].…”
Section: Introductionmentioning
confidence: 99%
“…An early study of tunneling into a TLL was reported by Oreg and Finkelstein 16 and since then there have been several works reported on the topic. [17][18][19][20][21][22][23] Amongst these, Jeckelmann in Ref. [20] applied dynamical density-matrix renormalization group (DDMRG) method to a 1D spinless fermion (SF) chain with nearest neighbor interaction and he confirmed that the bulk density of states (DOS) shows a power law suppression as → F ( F being the Fermi energy) in the gapless phase, as is expected from the TLL theory.…”
Section: Introductionmentioning
confidence: 95%